2009
DOI: 10.1016/j.obhdp.2009.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The enduring impact of transient emotions on decision making

Abstract: People often do not realize they are being influenced by an incidental emotional state. As a result, decisions based on a fleeting incidental emotion can become the basis for future decisions and hence outlive the original cause for the behavior (i.e., the emotion itself). Using a sequence of ultimatum and dictator games, we provide empirical evidence for the enduring impact of transient emotions on economic decision making. Behavioral consistency and false consensus are presented as potential underlying proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
172
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(186 citation statements)
references
References 42 publications
10
172
2
2
Order By: Relevance
“…This is an important topic for future research since, based on experimental evidence, moods can affect decisions (Isen, 1993;Slovic et al, 2002;Andrade & Ariely, 2009). Moreover, in an ingenious field study of university admissions staff, Simonsohn (2007) found that decisions reflected mood changes that could be attributed to fluctuations in weather patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important topic for future research since, based on experimental evidence, moods can affect decisions (Isen, 1993;Slovic et al, 2002;Andrade & Ariely, 2009). Moreover, in an ingenious field study of university admissions staff, Simonsohn (2007) found that decisions reflected mood changes that could be attributed to fluctuations in weather patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Rottenstreich and Hsee (2001), for example, showed that when outcomes of uncertain actions involve strong affect (positive or negative), reactions are relatively insensitive to large variations in the probability of the outcomes occurring (see also Hsee & Kunreuther, 2000;Slovic et al, 2002;Sunstein, 2003). Interestingly, Andrade and Ariely (2009) find that decisions based on fleeting incidental emotions can also affect future decisions even after the initial emotion has subsided.…”
Section: Introductionmentioning
confidence: 99%
“…Carryover effects of emotions and self-herding suggest that incidental emotions not only directly affect decisions at an unconscious level, but also indirectly spillover on other subsequent choices and actions taking place long after the initial emotional experience (Harlé & Sanfey, 2007;Lerner, Small, & Loewenstein, 2004). This is because, when we look back to our initial behavior, we tend to misattribute it to some of our deep preferences rather than to a fleeting emotion, and we choose our subsequent actions to follow suit the same inferred path (Andrade & Ariely, 2009). For instance, subjects who first watched a video that induced anger were not only more likely to reject unfair offers in a following, unrelated, ultimatum game than subjects who watched a happy video; but also made fairer offers to their partners in a subsequent dictator game, and even in a second ultimatum game where they acted as proposers (Andrade & Ariely, 2009).…”
Section: Promoting Spilloversmentioning
confidence: 99%
“…Angered individuals are more willing to reject offers in an ultimatum bargaining game and consequently make less money (16,17). Anger also significantly affects behavior in the repeated prisoner's dilemma games (18,19) and power-to-take games (20).…”
mentioning
confidence: 99%